Use Of Information Technology To Increase Sales In Mandepo Coffee MSMEs - Wira Herdika Firliansyah P.H; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Current developments in information technology are able to provide quite large results regarding increasing sales of MSMEs. This has inspired entrepreneurs to start utilizing information technology to expand their markets and as a means of promoting their business products. In the Mandepo Coffee business, the owner only sells his products in the market and places them in several stalls because he doesn't know how to use information technology to increase sales of his products. The solution is to provide training on how to utilize social media and e-commerce in order to maximize sales. The aim of this research is to educate and make MSME stakeholders aware of the use of information technology to increase sales of their business products.